2004
DOI: 10.1007/s00120-003-0492-3
|View full text |Cite
|
Sign up to set email alerts
|

Indinavir-Urolithiasis bei HIV-positiven Patienten

Abstract: HIV positive patients with renal colic or renal insufficiency and roentgenological absence of radio-opaque stone formations should make the urologist consider indinavir urolithiasis as a possible diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
1
0
2
Order By: Relevance
“…This was mainly decided in order to secure unobstructed drainage of the kidney during the following phase of forced hydration as urological symptoms developed in only 8% of patients treated with indinavir [13]. Besides Berns et al reported [12] that in one out of two patients indinavir crystalluria was demonstrated, requiring urologic intervention to relieve bilateral obstruction.…”
Section: Discussionmentioning
confidence: 97%
“…This was mainly decided in order to secure unobstructed drainage of the kidney during the following phase of forced hydration as urological symptoms developed in only 8% of patients treated with indinavir [13]. Besides Berns et al reported [12] that in one out of two patients indinavir crystalluria was demonstrated, requiring urologic intervention to relieve bilateral obstruction.…”
Section: Discussionmentioning
confidence: 97%
“…In den Titeln einschlägiger, vielfach aufgelegter Lehrbücher [75,76] des Fachgebiets Urologie sowie neueren Übersichtsarbeiten [77][78][79][80][81][82][83][84] und Beiträgen in Lehr-und Handbüchern [85][86][87][88] sind Geschlechtskrankheiten, Tuberkulose und AIDS bedeutsam.…”
Section: Die Historisch-fachliche Rezeption Von Seuchen Innerhalb Derunclassified
“…Das Problem der Indinavir-Steine (Crixivan ® ; [153,154]), die durch eine HIV-Therapie entstehen, ist Teil der 2018 neu überarbeiteten Leitlinie Urolithiasis des Arbeitskreis Harnsteine der Akademie der Deutschen Urologen der Deutsche Gesellschaft für Urologie e. V. DGU [155]. Die Erkrankung spielt ebenfalls bei facheinschlägigen Hygienerichtlinien und Instrumentenaufbereitung seit den 1980er-Jahren eine wichtige Rolle [156,157].…”
Section: Aidsunclassified